Sikap, Norma Subjektif, dan Kontrol Perilaku Terhadap Niat Membeli Produk Kosmetik Halal oleh Konsumen Muda - Dinesa Rahmavita Ayu Sukma; Harmanda Berima Putra; Bambang Sutejo (Journal of Management and Bussines (JOMB), 2023)
The purpose of this study was to determine the effect of attitudes, subjective norms, and behavioral control on the intention to buy halal cosmetic products by young consumers. Quantitative methods were used in this study and data were measured using a Likert scale. Sampling using purposive sampling method with sample criteria and obtained a sample of 170 people. The results showed that the Adjusted R Square value was 0.695 and the calculated F value was 129.180 with a significance level of less than 5%. In conclusion, attitude and behavioral control have a significant positive effect on purchase intention, while subjective norms have no significant positive effect on purchase intention. Keywords: Behavior Control, Purchase Intention, Subjective Norm, Attitude